Soil management in pera sweet orange ( Citrus sinensis) orchard - Vasconcellos, Hélio de Oliveira; Araújo, Celso Monnerat; Souza Britto, Dirce P.P de (Pesquisa Agropecuaria Brasileira, 2014)
Hoeing, herbicides, mulching, and permanent green cover with Pueraria javanica Benth and Centrosema pubescens Benth, were treatments investigated in a soil management trial of a Pera sweet orange orchard. Data on yield and fruit quality were collected for five consecutive years; a statistical analysis showed significant increases in yield and weight of fruit when mulching. The yield in juice was reduced in the plots with green cover although no treatment affected the acid content. The application of herbicides to the Centrosema green cover produced higher juice solids ratio which was significantly increased by the green covers in only two of the crops harvested.